Kegagalan Upaya Mediasi Antara Armenia Dan Azerbaijan Dalam Konflik Nagorno-Karabakh - Fatoni, Muhamad Afi; Rosyidin, Mohamad (Journal of International Relations, 2019)
After collapse of the Soviet Union, two small republics in the Caucasus region named Armenia and Azerbaijan were involved in a bloody conflict to fight for an autonomous region called Nagorno-Karabakh. The ceasefire finally succeeded with the help of mediation by Russia in 1994. Nonetheless, efforts to reach a peace agreement through the mediation of the OSCE Minsk Group have still not succeeded in achieving doubled progress. Both countries were questioned again engaging in fierce fighting for several years. This study uses the Conflict Triangle theory as a substitute for analyzing the dimensions of the Nagorno-Karabakh conflict that is being developed with the process of mediation that has been carried out by the OSCE Minsk Group. The author assumes that currently the mediation carried out only focuses on repairing clothes. The results obtained from this study are that mediation carried out by the OSCE Minsk Group can focus on mediation at the government level only, meanwhile mediation at the community level (track-two diplomacy) relating to contributions related to cultural programs and climate change is not implemented at all , which resulted in a breakdown in the mediation of the reluctance of the public from both sides to compromise.